PENGARUH LAMA MELAUT DAN JUMLAH HAULING TERHADAP HASIL TANGKAPAN IKAN PADA PERIKANAN GILLNET SKALA KECIL DI PEKALONGAN JAWA TENGAH - Wiyono, Eko Sri (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The high competition among fishermen have resulted decreasing fish catches. To ensure the continuity of his activity, fishermen perform a variety of fishing strategies such as adding a length time of fishing trip at the sea and increasing the number of hauling. To assess the impact of both factors have been conducted research on gillnet small-scale fisheries (<10GT) in Pekalongan fishing port. Results of this study indicate that length of fishing trip have influence on both total and per species fish catches. Although length of fishing time more longer, result of this study showed that length of fishing trips do not affect to the fish price. On the other hand the results of this study indicate that the number or frequency of hauling apparently had no effect on either total catch or per species.